Genre features of the bibliographic section in “The Bulletin of the Novgorod Zemstvo” - Barashkova Daria Sergeevna (Studia Humanitatis)
The article examines the role and significance of “The Bulletin of the Novgorod Zemstvo” as an example of regional periodicals in Russia at the end of the 19th and the beginning of the 20th centuries. The main topic of the article is the study of “The press review” genre characteristics. This section includes reviews of literary works as well as biographies of the authors. The problem lies in the relatively insufficient attention given to regional publications of the aforementioned period and their contribution to cultural enlightenment. The aim of the work is to identify how “The Bulletin” contributed to the formation of literary preferences and the improvement of education levels among ordinary people.